2019
DOI: 10.1101/gr.243477.118
|View full text |Cite
|
Sign up to set email alerts
|

BiosyntheticSPAdes: reconstructing biosynthetic gene clusters from assembly graphs

Abstract: Predicting biosynthetic gene clusters (BGCs) is critically important for discovery of antibiotics and other natural products. While BGC prediction from complete genomes is a well-studied problem, predicting BGCs in fragmented genomic assemblies remains challenging. The existing BGC prediction tools often assume that each BGC is encoded within a single contig in the genome assembly, a condition that is violated for most sequenced microbial genomes where BGCs are often scattered through several contigs, making i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 51 publications
1
49
0
Order By: Relevance
“…3A). It was previously shown that NRPS/PKS gene clusters often result in fragmented assemblies from short reads (22). While we saw 1,100 CD and 939 KS domains in total on contigs of Ͼ10 kb across our genomes, we also saw 555 CD and 417 KS domains on contigs of Ͻ10 kb, indicating that a large fraction of BGCs in the genomes of these microbes may not have been analyzed here.…”
Section: Resultsmentioning
confidence: 52%
“…3A). It was previously shown that NRPS/PKS gene clusters often result in fragmented assemblies from short reads (22). While we saw 1,100 CD and 939 KS domains in total on contigs of Ͼ10 kb across our genomes, we also saw 555 CD and 417 KS domains on contigs of Ͻ10 kb, indicating that a large fraction of BGCs in the genomes of these microbes may not have been analyzed here.…”
Section: Resultsmentioning
confidence: 52%
“…We found an overwhelming majority of C and KS domain sequences having sequence identity scores well below 85% to their predicted natural product ( Supplementary Tables S2, S3 ). It was previously shown that shotgun metagenomics may lead to fragments of NRPS/PKS gene clusters which may account for the large number of low identity scores ( Meleshko et al, 2019 ). On the contrary, scores below the threshold may imply potential novelty in NRPS and PKS products, although further studies would be required to assess the extent of this novelty.…”
Section: Resultsmentioning
confidence: 99%
“…No BGC was shared between all six strains, however, the BGC predicted by antiSMASH to encode enzymes required for biosynthesis of an N -tetradecanoyl tyrosine-like compound was identified in all strains, except for P. maricaloris LMG 19692 T . Since only two of the genomes are complete genomes, it is likely that this BGC would also be identified in P. maricaloris LMG 19692 T , as BGCs are known to be difficult to detect in contig-based genomes due to the repeat regions in BGCs 30 . The predicted BGCs in all six strains shared little to no sequence homology to already known BGCs (data not shown).…”
Section: Resultsmentioning
confidence: 99%